REVIEW OF THE BOOK: THE WAR THAT ENDED PEACE. HOW EUROPE ABANDONED PEACE FOR THE FIRST WORLD WAR (Journal of the Spanish Institute for Strategic Studies, 2018)
A bibliographic comment for this book writen by Margaret MacMillan